2011
DOI: 10.1167/iovs.10-6770
|View full text |Cite
|
Sign up to set email alerts
|

Refractive Error in Nigerian Adults: Prevalence, Type, and Spectacle Coverage

Abstract: Uncorrected refractive errors are an important cause of visual impairment in Nigeria, and services must be dramatically improved to meet the need.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
68
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(82 citation statements)
references
References 41 publications
7
68
1
1
Order By: Relevance
“…23 the ''unmet needs'' for RS and CSS, as well as spectacle coverage and cataract surgical coverage. The spectacle coverage rates (based on the ''better-seeing eye'' definition) in our cohort (42.7%-65.5%) were slightly lower than reported in Taiwan (71.2%), 28 but higher than reported in many developing countries (e.g., 3.4% in Nigeria, 29 3.0% in Bangladesh, 30 6.2% in Pakistan, 31 and 17.4% in India 32 ). Likewise, our cataract surgical coverage rates (34.5%-63.4%) were slightly lower than reported in Latinos in the United States (65.7%), 33 but generally higher than reported in developing regions (well below 50%).…”
Section: Discussioncontrasting
confidence: 77%
“…23 the ''unmet needs'' for RS and CSS, as well as spectacle coverage and cataract surgical coverage. The spectacle coverage rates (based on the ''better-seeing eye'' definition) in our cohort (42.7%-65.5%) were slightly lower than reported in Taiwan (71.2%), 28 but higher than reported in many developing countries (e.g., 3.4% in Nigeria, 29 3.0% in Bangladesh, 30 6.2% in Pakistan, 31 and 17.4% in India 32 ). Likewise, our cataract surgical coverage rates (34.5%-63.4%) were slightly lower than reported in Latinos in the United States (65.7%), 33 but generally higher than reported in developing regions (well below 50%).…”
Section: Discussioncontrasting
confidence: 77%
“…24,25 Additionally, a recent review of global epidemiologic studies found rates ranging from 15.8 to 48.9% for astigmatism greater than 0.5 to 1.0 diopters. 33 In our study population, approximately 12% had astigmatism greater than 2.00 diopters, and this group had smaller gains in reported vision function and quality of life at follow-up, controlling for demographic and vision-related characteristics. Subgroup analyses show that there clearly are some who would be best served with custom spectacles.…”
Section: Discussionmentioning
confidence: 63%
“…Beijing or Taiwan and in studies from Nigeria, Bangladesh and Argentina [9,16,17,20,33,34,35]. All these studies were population based and not hospital based.…”
Section: Discussionmentioning
confidence: 99%